Proposing a Simple Radiation Scale for the Public: Radiation Index - Cho, Gyuseong; Kim, Jong Hyun; Park, Tae Soon; Cho, Kunwoo (Nuclear engineering and technology, 2017)
A new radiation scale is proposed. With empathy toward the vast majority of people who are not well versed in radiation and related matters, and thus suffering from misunderstanding that breeds unnecessary fear of radiation, the aim of proposing a new radiation scale, radiation index (RAIN), is to put the general public at ease with the concept of radiation. RAIN is defined in dimensionless numbers that relate any specific radiation dose to a properly defined reference level. As RAIN is expressed in plain numbers without an attached scientific unit, the public will feel comfortable with its friendly look, which in turn should help them understand radiation dose levels easily and allay their anxieties about radiation. The expanded awareness and proper understanding of radiation will empower the public to feel that they are not hopeless victims of radiation. The correspondence between RAIN and the specific accumulated dose is established. The equivalence will allow RAIN to serve as a common language of communication for the general public with which they can converse with radiation experts to discuss matters related to radiation safety, radiation diagnosis and therapy, nuclear accidents, and other related matters. Such fruitful dialogues will ultimately enhance public acceptance of radiation and associated technologies.